The Role of Intellectual Capital, Intrinsic Motivation, and Competence on Service Performance: Empirical Studies at Jakarta Private Universities - Suryono Efendi; Edy Rahardja (GoAcademica Research & Publishing, 2021)
This study aims to determine the role and influence of the variables of intellectual capital, intrinsic motivation and Competence on the services of private university lecturers in Jakarta. This research uses quantitative research with a descriptive analysis approach. The population in this study were lecturers of the Faculty of Economics and the College of Economics at Kopertis Region III DKI Jakarta. The criteria for selecting the sample are: Lecturer of the Faculty of Economics and the College of Economics at Kopertis Region III DKI Jakarta, and the status of permanent lecturers of foundations and Seconded Lecturers (DPK) at Kopertis area III DKI Jakarta and at least have the academic position of Lector. The sample selection in this study used purposive sampling. The data collection method used in this research is structured interviews using a Personal Questionnaire. Primary and secondary data were analyzed in this study. The Validity Test, the Reliability Test, the Multiple Linear Regression Test, and Hypothesis Testing are used to analyze the data in this study (F Test and Partial Hypothesis Testing). The findings and analyses suggest that there is a positive and significant relationship between Intellectual Capital, Intrinsic Motivation, and Competence and the service performance of private university lecturers in Jakarta.